The changes in feeling of loneliness after retirement among baby boomers and pre-boomers in Taiwan: Do work-family conflict before retirement and social engagement after retirement matter? - Chi Chiao; Pin-Han Kuo; Der-Chiang Li; Susan C. Hu (Elsevier, 2022)
Significance: Few studies have analyzed how loneliness-related factors differ across generations for older adults in non-Western societies. Building upon the stress process model, this study aimed to explore the relationships between work-family conflict before retirement, social engagement after retirement and changes in loneliness after retirement among retirees across two birth cohorts (Baby Boomers and pre-Boomers) in Taiwan. Methods: Data from the Taiwan Health and Retirement Study, a nationwide retired cohort sample collected from two waves between 2015/2016 and 2018/2019, was analyzed. A total of 2370 retirees aged 50-74 years were included in the analysis after excluding those who died or were lost to follow-up. Multivariate multinomial logistic models were used to estimate four types of changes in loneliness: (1) remaining not lonely, (2) becoming not lonely, (3) becoming lonely, and (4) remaining lonely. Results: About two-thirds of the retirees remained not lonely, and less than 10% maintained their feelings of loneliness across two waves. Multinomial logit models showed that both cohorts who experienced work-family conflict before retirement and stressful life events after retirement had higher odds of remaining lonely than those who remained not lonely. However, an increase in social engagement, especially social contact, appeared to be a protective factor against becoming and remaining lonely for both cohorts. Yet, work-related characteristics before retirement were significantly related to the changes in loneliness among pre-Boomers rather than Baby Boomers. Conclusions: The results suggest that work-family conflict before retirement produces an exacerbating effect; in contrast, social engagement after retirement is beneficial to not feeling lonely across two birth cohorts in Taiwan. This investigation highlights the importance of social stressors occurring before retirement because these have an effect on retirees' feelings of loneliness beyond individual socioeconomic status.